Production Monitoring System: A Case Study of Perpa Parquet Sdn. Bhd. - Mohd Ali Hanafiah, Siti Adiana (Universiti Teknologi Petronas, 2000)
The objective of this project is to develop a prototype system that could be used to monitor the stock of raw material as well as to monitor the performance of the first three phases of production line. Besides that the author did some research on how to present a production report. Current problem facing by Perpa Parquet Sdn Bhd is that there is no application that can monitor the accuracy of level of raw material in the company and the utilization and flow of the raw material and work in progress product is not well captured. Thus, this project will monitor the stock of raw material as well as the flow of material in production lines. The author suggested to create a system that can measure the stock quantity of raw material, monitor the achievement of the first three phases of production lines and produce a daily as well as the monthly production report.